Evaluation of the Maxillary Third Molars and Maxillary Sinus Using Cone-Beam Computed Tomography - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2018)
Objectives: The purpose of this study was to assess the relationship of the maxillary third molars to the maxillary sinus using cone-beam computed tomography (CBCT) in a Turkish population. Materials and Methods: A total of 300 right and 307 left maxillary third molars were examined using CBCT images obtained from 394 patients. Data including the age, gender, the angulation type, depth of the third molars, and horizontal and vertical positions of the maxillary sinus relative to the third molars were examined. Results: Among 394 patients, 215 (54.6%) were male and 179 (45.4%) were female. The most common angulation of impaction was vertical (80.2%). Based on the depth of the third molars in relation to the adjacent second molar, Class A was the most common. Regarding the relationships of the third molars with the maxillary sinus, vertical Type I (43.5%) and horizontal Type II (59.3%) were seen most frequently. There was a significant difference between the vertical and horizontal relationships (P < 0.05). Conclusions: Knowledge of the anatomical relationship between the maxillary sinus floor and maxillary third molar roots is important for removing a maxillary third molar. CBCT evaluation could be valuable when performing dental procedures involving the maxillary third molars.
Keywords: Cone-beam computed tomography; maxillary sinus; maxillary third molar; POSTERIOR TEETH; PANORAMIC RADIOGRAPHY; POSITION; IMPACTION; REMOVAL; POPULATION; AGE; CT